On Gonorynchus, Gonorhynchus, Gonorinchus, Gonorhinchus and Gonorrhynchus, and some other names of labeonine fishes (Teleostei: Gonorynchidae and Cyprinidae) - Kottelat, Maurice (Zootaxa, 2016)
The supposed cyprinid genus ‘Gonorhynchus McClelland, 1838’ does not exist; the name refers to Gonorhynchus Cuvier, 1816, which is a junior objective synonym of Gonorynchus Scopoli, 1777. The correct family-group name, authorship and date are: Gonorynchidae Fowler, 1941 (1848). Tariqilabeo Mirza & Saboohi, 1990 is the valid genus name for the South Asian species earlier placed in Crossocheilus or ‘Gonorhynchus’. The family-group names Garrae Bleeker, 1863 and Labeonini Bleeker, 1859 are declared nomina protecta and Platycarinae Macleay, 1841 is declared nomen oblitum.